Transaction management across data stores. (2018) - Jimenez-Peris, Ricardo; Patiño-Martinez, Marta; Brondino, Iván; Vianello, Valerio
Companies have evolved from a world where they only had SQL databases to a world where they use different kinds of data stores such as key-value data stores, document-oriented data stores and graph databases. This scenario presents new challenges such as data model heterogeneity and data consistency. There could be inconsistencies in case of failures during business actions requiring to update data scattered across different data stores owing to the lack of transactional consistency across data stores. In this paper we propose an ultra-scalable transactional management layer that can be integrated with any data store with multi-versioning capabilities. This layer has been developed in the context of the FP7 CoherentPaaS European Project where it was integrated with six different data stores, three NoSQL data stores and three SQL-like databases. We particularly focus on the ultra-scalable transaction management API and how it can be easily integrated in any versioned data store.